How aid helps achieve MDGs in Africa: The case of primary education - Yogo, Thierry Urbain (International Food Policy Research Institute, 2015)
Since 2000, Official Development Assistance has played a crucial role in efforts to achieve the global MDGs. This is especially true in Sub-Saharan Africa (SSA), the world’s largest recipient of foreign aid. This paper assesses the effectiveness of aid in achieving universal primary education in Sub-Saharan Africa. The impact of aid is assessed for a sample of 35 SSA countries from 2000-2010. The results suggest that higher aid for education significantly increases primary education completion rates. This result is robust to the use of various methods of estimation, the inclusion of instruments to account for the endogeneity of aid, and the set of control variables included in regressions.